ANALISIS PERAN STAKEHOLDER PEMERINTAH DAERAH DALAM STRATEGI KOMUNIKASI CITY BRANDING: “PONOROGO ETHNIC ART OF JAVA” - Setiawan, Veri; Nurhana Marantika; Mohammad Abdul Hamid Alfarizi Al Ma'arif Nur (LP3M IAI Al-Qolam, 2024)
Ponorogo Regency is one of Indonesia's cities rich in Javanese ethnic culture and art. One aspect that becomes potential in City branding Ponorogo is the tagline